‘A Peculiarly English Institution’:1 Work, Rest, and Play in the Labour Church - Cowman, Krista (Studies in church history, 2002)
The Labour Church held its first service in Charlton Hall, Manchester, in October 1891. The well-attended event was led by Revd Harold Rylett, a Unitarian minister from Hyde, and John Trevor, a former Unitarian and the driving force behind the idea. Counting the experiment a success, Trevor organized a follow-up meeting the next Sunday, at which the congregation overflowed from the hall into the surrounding streets. A new religious movement had begun. In the decade that followed, over fifty Labour Churches formed, mainly in Northern England, around the textile districts of the West Riding of Yorkshire and East Lancashire. Their impetus lay both in the development and spread of what has been called a socialist culture in Britain in the final decades of the nineteenth century, and in the increased awareness of class attendant on this. Much of the enthusiasm for socialism was indivisible from the lifestyle and culture which surrounded it. This was a movement dedicated as much to what Chris Waters has described as ‘the politics of everyday life …. [and] of popular culture’ as to rigid economistic doctrine. This tendency has been described as ‘ethical socialism’, although a more common expression at the time was ‘the religion of socialism’.